2005
DOI: 10.1074/jbc.m411483200
|View full text |Cite
|
Sign up to set email alerts
|

The Dileucine Motif at the COOH Terminus of Human Multidrug Resistance P-glycoprotein Is Important for Folding but Not Activity

Abstract: These results show that the dileucine motif is not a plasma membrane targeting signal. The COOH terminus is required for proper folding of P-gp but not for activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
(60 reference statements)
2
15
0
Order By: Relevance
“…P-glycoprotein is reported to appear in western blot as glycosylated 170-kDa and unglycosylated 140-kDa bands [7]. Similarly, in our study, we found that P-glycoprotein appeared mainly as the unglycosylated 140-kDa form in SGC7901 cells, while in both SGC7901/VCR and SGC7901/ADR cells it appeared as the glycosylated 170-kDa form (Fig.…”
Section: 3supporting
confidence: 87%
See 1 more Smart Citation
“…P-glycoprotein is reported to appear in western blot as glycosylated 170-kDa and unglycosylated 140-kDa bands [7]. Similarly, in our study, we found that P-glycoprotein appeared mainly as the unglycosylated 140-kDa form in SGC7901 cells, while in both SGC7901/VCR and SGC7901/ADR cells it appeared as the glycosylated 170-kDa form (Fig.…”
Section: 3supporting
confidence: 87%
“…carcinoembryonic antigen (CEA) for colon cancer, prostate specific antigen (PSA) for prostate cancer and HER2 for breast cancer [4]. Interestingly, many classical MDR related molecules, including P-glycoprotein (P-gp), multidrug resistance-associated protein 1 (MRP1), and breast cancer resistance protein (BCRP) are also glycoproteins and glycosylation could affect their activities or functions, which, together with the profound importance of glycosylation in bioprocesses, suggest that glycosylation would play an important role in MDR of gastric cancer and glycoproteins may present as potential markers [5][6][7][8]. Recently, Di Michele et al screened the differential expressed glycoproteins between drug sensitive and resistant cell lines and found 4 glycoproteins remarkably upregulated in drug resistant cells as putative biomarkers for paclitaxel resistance in ovarian cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dileucine motifs are commonly involved in protein trafficking but usually at the level of the trans-Golgi network, endosomes, plasma membrane, and lysosomes (21). However, dileucine motifs also have been shown to play a role in ER trafficking (22)(23)(24)(25)(26)(27)(28).…”
Section: Salm1 Axonal Versus Dendritic Targeting Is Regulated By Pdz-bd-mentioning
confidence: 99%
“…Studies of other integral membrane proteins have identified amino acids in their intracellular C termini that are associated with folding and/or trafficking (7, 16 -26). In a number of cases, hydrophobic amino acids, particularly dileucine motifs, have been shown to be involved in these processes (16,17,19,22,23,25). A multiple alignment of Slc12 amino acid sequences reveals a C-terminal sequence pattern that is conserved in all vertebrate NKCCs, NCCs, and KCCs, as well as in a variety of Slc12 homologues from other nonvertebrate species, specifically xxxxhhhhRGxxxxVhThYx, where h and x represent hydrophobic and variable amino acids, respectively.…”
mentioning
confidence: 99%